Adsorption of carbon dioxide by a novel amine impregnated ZSM-5/KIT-6 composite. Issue 86 (28th November 2017) - Lin, Zhifeng; Wei, Jianwen; Geng, Linlin; Mei, Dejun; Liao, Lei
Abstract : Novel amine impregnated ZSM-5/KIT-6 composites exhibited excellent CO2 adsorption performance. Abstract : A novel amine modified composite was fabricated for CO2 capture. Tetraethylenepentamine (TEPA) or polyethyleneimine (PEI) was selected to modify the micro/mesoporous ZSM-5/KIT-6 composite (ZK). With the porous nature of the support, large amine loadings from 50 to 80% were expected via a typical impregnation step. The CO2 adsorption performance was investigated by thermal gravimetric analysis (TGA) in mixed gases (15% CO2 and the balance is N2 ) at 30–90 °C. With higher nitrogen content and better texture properties (surface area and total pore volume), TEPA-loaded materials exhibited better adsorption capacities than PEI-loaded materials. In the two series of samples, ZK-TEPA-60 and ZK-PEI-60 displayed outstanding CO2 capture, with capacities as high as 5.32 and 4.59 mmol g −1 at 60 and 75 °C, respectively. ZK-TEPA-60 demonstrated relatively rapid kinetics and a higher enthalpy. The materials we designed displayed excellent CO2 adsorption performance in comparison with other amine modified solid materials, indicating the prospects of these adsorbents for CO2 capture from flue gas.